The first Register in Europe of Allergic Urticaria and Anaphylaxis Caused by Erythritol (Revista de Medicina Clinica, 2021)
We present the case of a 61-year-old woman with anaphylaxis after ingesting ice creams containing erythritol as a sweetener. After a detailed study of the ingredients of the ice cream after each episode, the only component in common was erythritol. This sweetener has recently been used in Europe as an artificial additive in many types of food and drink, mainly because it does not contain calories. Therefore, food and drink additives should be included in the differential diagnosis of food allergic reactions. This is the first record of an allergic reaction caused by erythritol in Europe.
Keywords: anaphylaxis; erythritol; food sweeteners